Analyzing the content of the websites of RAS Siberian Branch research institutions - L. B. Shevchenko; Л. Б. Шевченко (Scientific and Technical Libraries, 2022)
The analysis of websites/web-pages of content of SB RAS research institutions is based on the content assessment checklist developed specifically for this study. The checklist comprised 50 questions divided in 5 sections: website information, web-page design and functions, content and web-services. The websites of Novosibirsk, Buryat, Irkutsks, Kemerovo, Krasnoyarsk, Omsk, Tomsk, Yakutsk and Tyumen research centers were selected for the study, 44 library websites altogether. The online survey was conducted within the study comprising two questions: Who manage and maintain the website/web-page of your library? Is this library website management strategy efficient? The respondents were also asked to propose on how to improve mangement of the institutional website. The web-content assessment enables to reveal problems and trends which would be useful for re-designing the library websites of research institutions. The author offers recommendations based on the study findings. Контент-анализ веб-сайтов/страниц библиотек научных учреждений СО РАН проведён на основе контрольного списка оценки контента вебсайта библиотеки, разработанного специально для настоящего исследования. Контрольный список содержал 50 вопросов, разделённых на пять разделов: информация о сайте, дизайн и функции веб-страницы, контент и веб-услуги. Исследовались веб-сайты/страницы библиотек НИУ следующих научных центров: Новосибирского, Бурятского, Иркутского, Кемеровского, Красноярского, Омского, Томского, Якутского и Тюменского. Всего проанализировано 44 сайта библиотек. В рамках исследования был проведён онлайн-опрос, включающий два вопроса: «Кто занимается управлением и ведением веб-сайта/страницы вашей библиотеки?» и «Эффективен ли, по вашему мнению, такой способ ведения веб-страницы библиотеки?», а также пункт с предложениями по оптимизации ведения веб-страницы библиотеки НИУ. Оценка веб-контента позволит помочь в определении тенденций и проблем современного состояния вебстраниц библиотек НИУ, что может быть полезным при редизайне ...